Background of the values for compressive strength of masonry acc. to EC 6 – evaluation of data / Hintergrund der Druckfestigkeitswerte für Mauerwerk im Eurocode 6 – Datenauswertung. Issue 3 (June 2014) - Jäger, Wolfram; Pech, Anton
Abstract In accordance with EN 1996‐1‐1 [1] the compressive strength of masonry is determined with the help of power functions. For this purpose, the standard includes values in Table 3.3 which were established by evaluating available test values in 2001/2002. In this article the theoretical background for the evaluation of the database is explained and a practical procedure is introduced which was applied at the time in order to be able to list values in EN 1996‐1‐1. This article does not discuss individual combinations of masonry units and mortar. It only presents in summary the methodology and the underlying mathematical basis. The purpose of this contribution is to provide the countries in need of specific evaluations support for the anticipated update and adaptation of EC 6.